Effects of habitat characteristics on the growth of carrier population leading to increased spread of typhoid fever: A model - J.B. Shukla; Ashish Goyal; Shikha Singh; Peeyush Chandra (Journal of Epidemiology and Global Health, 2019)
In this paper, a non-linear model is proposed and analyzed to study the effects of habitat characteristics favoring logistically growing carrier population leading to increased spread of typhoid fever. It is assumed that the cumulative density of habitat characteristics and the density of carrier population are governed by logistic models; the growth rate of the former increases as the density of human population increases. The model is analyzed by stability theory of differential equations and computer simulation. The analysis shows that as the density of the infective carrier population increases due to habitat characteristics, the spread of typhoid fever increases in comparison with the case without such factors.